Open Doors - Gūtmane , Zanda; Ostups, Artis (Colloquia, 2021)
Professor Zanda Gūtmane from the University of Liepaja (Latvia) Is Interviewed by Artis Ostups, Editor-in-Chief of the Latvian Online Magazine for Literature and Philosophy Punctum